Safety and efficacy of a feed additive consisting of copper lysinate sulfate for all animal species (Phytobiotics Futterzusatzstoffe GmbH) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Roberto Edoardo Villa; Giovanna Azimonti; Eleftherios Bonos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Ronette Gehring; Boet Glandorf; Maryline Kouba; Marta López‐Alonso; Francesca Marcon; et al. (EFSA Journal)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of copper lysinate sulfate as nutritional feed additive for all animal species. The additive has not yet been authorised in the EU. The FEEDAP Panel concluded that the additive copper lysinate sulfate is safe for all animal species and categories at the respective maximum authorised total copper levels in feed. In the absence of reliable deposition data, the FEEDAP Panel could not conclude on the safety of the additive for the consumer. In the absence of data, the FEEDAP Panel could not conclude on the eye irritation potential of the additive. The Panel concluded that the additive is not a skin irritant and thus it should be considered a skin and respiratory sensitiser; inhalation and dermal exposure are considered a risk. The FEEDAP Panel concluded that the use of the additive under the proposed conditions of use is safe for the environment. The Panel was not in the position to conclude on the efficacy of the additive at the maximum authorised inclusion level.